Individual'no-tipovye charakteristiki reakcij echtoval'šcikov na sportivnye nagruzki - Rodionova, I. A.; Shalupin, V. I. (Vestnik Moskovskogo gorodskogo pedagogiceskogo universiteta. Serija «Estestvennye nauki», 2015)
In a study conducted among highly qualified fencers (female foil fencers), the authors studied peculiarities of reactions to athletic exercises. We compared the various stages of the annual cycle: basic training, the main competitions of the year. The authors established individual and typical features of adaptation of sportswomen to the conditions of preparation for competitions and participation in them.